Multidrug Resistance: Are We Still Afraid of the Big Bad Wolf - Abdulelah Alhazza; Adenike Oyegbesan; Emira Bousoik; Hamidreza Montazeri Aliabadi (Pharmaceuticals)
After the era of multidrug resistance (MDR) against cytotoxic chemotherapy, the development of resistance against newly developed molecularly targeted drugs also seems inevitable. While the mechanisms involved in resistance against these two categories of anticancer drugs are different, the principles are similar: inherent resistance (also known as primary resistance) is a result of heterogeneity in cancer cells where a subpopulation of the cells do not show a favorable initial response to the drug, while acquired resistance (or secondary resistance), as the name suggests, is developed after repeated treatments due to the plasticity of cancer cells. Despite the introduction of a variety of molecularly targeted drugs to clinical practice, chemotherapy is still at the forefront of the battle against cancer. In this manuscript, we review the major mechanisms involved in MDR and resistance against different categories of molecularly targeted drugs separately, and review some of the strategies studied to overcome the resistance against cancer therapy. While MDR mechanisms have been reviewed previously, the molecular mechanisms of resistance to the latest generations of anticancer drugs are rarely reviewed as a group, and the connection between the two categories of resistance is often missing in this type of publication. Our aim is to illustrate a comprehensive picture of what the landscape of cancer treatment is today with respect to resistance. While this picture seems bleak, and it is the common belief that resistance is inevitable, understanding the mechanisms involved could potentially lead to more efficient approaches to overcoming this so far unbeatable obstacle.